Detection on common deletional alpha thalassaemia in pregnant women by polymerase chain reaction techniques - Fathma Abdullah, Nurul Ain (2015)
Thalassaemia is the most common inherited disorder worldwide and represent as a major health problem in many areas and approximately 4.5%- 6% of Malaysians are carrier of this genetic disorder. There are two type of thalassaemia which α and β thalassemia. α-thalassaemia either the deletion of a single or double α-globin gene deletion that is located at position 16p3.3 is the one of the most common genetic disorder in the world. In Malaysia, the incidence is 4.5%. The aims of this study were to identify and characterised the common deletional type cases of α-thalassaemia in Malay pregnant women at HUSM by molecular method. A total of 200 Malay pregnant women who attended for an antenatal check-up at Hospital Universiti Sains Malaysia were screened for α-thalassaemia. DNA was extracted from 200 pregnant women blood using commercial DNA extraction kit prior to PCR amplification. Of these, 16 were excluded as they were diagnosed as β- thalassaemia/Hb E trait. Out of 184 genomic DNA, 17 (9.2%) were possessed α-thalassaemia deletion. The genotype could be identified to - α3.7/αα in 15 (8.1%) and --SEA/αα in 2(1.1%). While -α4.2 kb deletion and --THAI deletion was not detected in our subjects. Thus, the most common deletion in the Malays pregnant women were -α3.7 followed by --SEA. The molecular method has been established to detect these carriers. The presence of two gene deletion evidenced by --SEA. showed the importance to screen α- thalassaemia among Malay pregnant women and subsequent screening patients' spouse to exclude hydrops fetalis. Detection of --SEA α-thalassaemia by PCR techniques is convenient, and suitable to be used as a confirmatory test.